Comparison of agents and sensitivity profile in urinary tract infection in diabetic and non-diabetic patients - Debora da Silva Krenke; Simão Augusto Lottenberg; Marines Dalla Valle Martino; Jacyr Pasternak (Einstein (São Paulo), 2007)
Objective: To study diabetic and non diabetic patients in UTI, regardingthe prevalence of broad spectrum beta-lactamase producing pathogensand quinolone resistance. Methods: Inclusion criteria for this studywas the presence of positive urine culture and fasting glucose equal toor above 126 mg/dl and below 100 mg/dl. We managed to include 494patients, 210 diabetics and 284 non-diabetics. Results: Escherichiacoli was the most frequently found pathogen in both diabetic andnon-diabetic groups, and significantly more frequent in non diabeticpatients (p = 0.0001) – 60% to 31% when compared to their diabeticcounterparts. Candida albicans infecting the urinary tract was foundin 30% of diabetics and in 16% of non-diabetics (p = 0.003). Broadspectrum beta-lactamase production was more frequently present inKlebsiella pneumoniae, however without significant difference betweenthe groups. Broad spectrum beta-lactamase production was morefrequent in diabetic patients (12%) than in non-diabetics (4%) (p =0.03). Quinolones resistance was more common in diabetics (40%)when compared to non-diabetics (14%) (p = 0.0001). Escherichiacoli is one of the pathogens more frequently found in patients withUTI. Conclusion: Diabetics have a greater likelihood of developingfungal urinary tract infection by Candida albicans, have more broadspectrum beta-lactamase producing Escherichia coli and more quinolone-resistant pathogens.